Lipid-Coated Nanocrystals as a Tool for Improving the Antioxidant Activity of Resveratrol - Monica Argenziano; Irfan Aamer Ansari; Elisabetta Muntoni; Rita Spagnolo; Anna Scomparin; Roberta Cavalli (MDPI AG, 2022)
Trans-resveratrol, a polyphenolic phytoalexin found in various plant sources, has been the focus of increasing attention in recent years because of its role in the prevention of many human diseases, and particularly because of its antioxidant properties. However, the in vivo effect of trans-resveratrol after oral administration is negligible when compared to its efficacy in vitro, due to its low bioavailability. Moreover, it presents stability issues as it is an extremely photosensitive compound when exposed to light. This work aims to develop lipid-coated nanocrystals in order to improve the antioxidant activity and bioavailability of trans-resveratrol. Lipid-coated trans-resveratrol nanocrystals with sizes lower than 500 nm, spherical shapes and smooth surfaces were obtained via a milling method. They showed a faster dissolution rate than the coarse trans-resveratrol powder. The antioxidant properties of trans-resveratrol were not impaired by the milling process. The in vivo pharmacokinetics of lipid-coated trans-resveratrol nanocrystals were evaluated after oral administration to rats, with a commercial Phytosome® formulation being used for comparison purposes. An increase in the trans-resveratrol area under the curve was observed and the lipid-coated nanocrystal formulation led to an enhancement in the oral bioavailability of the compound.